China's engagement in Pakistan, Afghanistan, and Xinjiang: Will China's root cause model provide regional stability and security? - Lars Erslev Andersen; Yang Jiang (Danish Institute for International Studies (DIIS), 2018)
In the latest policy report in DIIS's Defence and Security Studies series, Lars Erslev Andersen and Yang Jiang discuss the potential of China's approach to stabilising security conditions in Pakistan and Afghanistan through development. The report explores China's westward policy by analysing the opportunities and obstacles related to its flagship Belt and Road Initiative (BRI) in South Asia, in particular the China-Pakistan Economic Corridor (CPEC). One aspect of the philosophy behind the CPEC is that lifting people out of poverty by providing them with better opportunities for jobs and incomes and hence improved living conditions will reduce the attractions of violent extremism and the inclination to indulge in it, thereby enhancing stability. This so-called Root Cause model draws on China's experience of successfully lifting more than 600 million of its own citizens out of poverty due to the reform policy that has changed China rapidly over the past forty years, especially in the big cities in eastern China. However, the model has had mixed results in western China, especially in Xinjiang province. As this issue can shed light on the kinds of problems that China will face in Afghanistan and Pakistan, the report explores the situation in Xinjiang by investigating how it is conducting its policy there. The report outlines this development, which brings the Root Cause model into question to some extent, thus identifying some of the challenges that China will face in trying to stabilise conflict-torn parts of Pakistan and Afghanistan "the Chinese way". Following these observations, the report takes a closer look at China's economic diplomacy in Afghanistan. The last section discusses China's increasing role in mediating between Afghanistan, Pakistan and the Taliban. Whether the Chinese approach to the situation in Pakistan and Afghanistan proves to be a sustainable way of providing stability and achieving results is the question addressed in the report's conclusion.
Keywords: 300